Penegakan Hukum terhadap Penyebaran Konten Asusila di Media Sosial berdasarkan UU No. 19 Tahun 2016 tentang ITE: Studi di Polrestabes Bandung - Aldira Dean Pratama; Dian Rachmat Gumelar; Wawan Kurniawan (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The development of information technology has transformed social media into a massive communication platform that facilitates the exchange of information, but it also opens opportunities for misuse, including the dissemination of obscene content that violates moral norms and potentially harms public morality. This study employs an empirical legal research method with a juridical-empirical approach to examine law enforcement against this phenomenon based on Law No. 19 of 2016 concerning Electronic Information and Transactions within the jurisdiction of Polrestabes Bandung. Primary data were obtained through an in-depth interview with Bripda Billy Fajar Pratama on January 17, 2026, while secondary data were collected through literature studies of statutory regulations, legal literature, and scientific journals. The data were analyzed using descriptive qualitative analysis. The results indicate that law enforcement practices follow the procedures stipulated in the Criminal Procedure Code, focusing on Article 27 paragraph (1) in conjunction with Article 45 of the ITE Law, emphasizing the act of content distribution by the perpetrator rather than the behavior of the victim, supported by expert testimony to verify the obscene content. Although the number of cases remains relatively small compared to other ITE offenses, several obstacles persist, including differences in perception between complainants and legal definitions, difficulties in obtaining digital evidence, and limited technical competencies. Law enforcement efforts include strengthening evidentiary processes through expert testimony, referring to the joint ministerial decree of three ministries, and promoting digital privacy awareness among the public as a preventive measure. Overall, law enforcement demonstrates adaptive characteristics but still requires institutional strengthening to effectively address the evolving dynamics of cybercrime